81.8k views
4 votes
1. Given s = 3x +t/r

rearrange the equation for x, in terms of r, s, and t
2. Given 5ax + b = C, rearrange the equation for x, in terms of a, b, and c.

1. Given s = 3x +t/r rearrange the equation for x, in terms of r, s, and t 2. Given-example-1
User Olonge
by
5.2k points

1 Answer

5 votes

Answer:

Explanation:

1). s =
(3x+t)/(r)

r.(s) =
r.((3x+t)/(r))

rs = 3x + t

rs - t = 3x


(rs-t)/(3)=(3x)/(3)


(rs-t)/(3)=x


x=(1)/(3)(rs-t)

2). 5ax + b = c

(5ax + b) - b = c - b

5ax = c - b


(5ax)/(5a)=(c-b)/(5a)

x =
(1)/(5)((c-b)/(a))

User Thanakron Tandavas
by
5.4k points